The Effectiveness of Pelvic Rocking Exercises With Birthing Ball on Labor Progress in Maternal in 2022 - Arfah Arfah; Feva Tridiyawati (International Journal of Medicine and Health, 2022)
Protracted labor is correlated with an increase in maternal and fetal motility, an increase in abnormalities in the physiology of labor, and an escalation in the rate of caesarean section delivery. In women with prolonged labor, there is an increased risk of death due to atonic uterus, birth canal lacerations, infection, fatigue, and shock, however in infants, prolonged labor is not associated with an increase in infant mortality, decreased APGAR score, trauma, and infection. With adequate physical and psychological preparation, the impact of prolonged labor can be reduced. The (PRE) is a bodywork involving waist and hip rotations. This research employs Systeematic Literature Reviews (SLR), a synthesis of systematic, clear, and comprehensive literature studies, by identifying, analyzing, and evaluating existing data using explicit research methods and incorporating critical review procedures into the selection study. The data consists of 6 national journals and 1 international publication indexed by Shiinta Indonesia and Scopus with Q2standard Results in 7 journals utilizing observation sheets and parttographs for data collection instruments. In one of the seven journals reviewed, the Pellvic Rocking Exercise technique was applied at TM 3 gestational age, between 34 and 35 weeks. When the laboring mother enters the first stage of the active phase, another publication employs the Pelvic Rocking Exercise technique. Conclusion: Pelvic Roccking Exercise is effective in shortening the active phase till the full opening of the cervix in primiparous moms. Pelvic rocking using a birth ball helps the baby to rotate into the optimal position and shortens the first stage of labor, therefore reducing labor pain and providing comfort to the mother. It is anticipated that health care workers will become facilitators for expectant mothers and provide physical support for the profession.